Healthy Lifestyle Motivators of Willingness to Consume Healthy Food Brands: An Integrative Model - Guerra-Velasquez, M; Escobar-Farfan, M (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
This study evaluated how healthy lifestyle motivators (MHLs) influence the Peruvian market’s willingness to consume healthy food (WCHBF). The main objective was to analyze the relationship of variables, such as attitude (ATT), perceived behavioral control (PBC), self-identity (SI), and moral norms (MN) with the WCHBF. This study adopted a quantitative, non-experimental, and cross-sectional approach, using a self-administered questionnaire for data collection. A total of 585 individuals participated. The participants were consumers of the Unión brand, which specializes in healthy food. A 5-point Likert scale was used to evaluate the key variables. For the analysis, IBM SPSS Statistics 25 programs were used to examine the demographic data and SmartPLS 4.1.0.9 was used to assess the conceptual model using partial least squares (PLS-SEM). The results showed that healthy lifestyle motivators positively influence the willingness to consume healthy food and ATT, PBC, SI, and MN variables. In turn, these variables significantly impact the willingness to purchase healthy food. The findings suggest that marketing campaigns should highlight these motivators to encourage the consumption of healthy food. The implications of this study reinforce the importance of understanding psychological factors in consumer decision-making. © 2025 by the authors.